PHENOLOGICAL TRAITS OF MANGROVE Kandelia obovata GROWN IN MANKO WETLAND, OKINAWA ISLAND, JAPAN - Kangkuso Analuddin; Andi Septiana; Sahadev Sharma; Akio Hagihara (International Journal of Sustainable Tropical Agricultural Sciences (IJSTAS), 2015)
Phenological traits of Kandelia obovata (S., L.) Yong was investigated on the basis of seasonal leaf recruit, leaf death and leaf growth. The seasonal leaf growth was estimated using the logistic growth curve. Leaf recruitment, leaf death and reproductive cycle were obtained by survey data. This study results showed that new leaf recruitment occurred during the year indicating high productivity of mangrove Kandelia obovata forest. The highest leaf recruit was in July, while it was the lowest in January. However, the highest leaf death was in August, whereas it was the lowest in January. Growth pattern of leaves varied among seasons as of winter leaves are taken longger time to get their maximum size, while other season leaves are taken short time to get their maximum size. Period from flowering to mature propagules of K. obovata trees is considered to be around 12 months, while most the propagules become mature in the next spring season (April and May), which indicated shorter reproduction cycle.